Evaluation of radiation-induced genotoxicity on hu-man melanoma cells (SK-MEL-37) by flow cytometry (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Micronucleus assay is a test used to evaluate genotoxic damage in cells, which can be caused by various factors, like ionizing radiation. Interactions between radiation energies and DNA can cause breakage, leading to use chromosomal mutations or loss of genetic material, important events that could be induced in solid tumors to mitigate its expansion within human body.  Melanoma has been described as a tumor with increased radio resistance.  This work evaluated micronuclei percentages (%MN) in human melanoma cells (SK-MEL-37), irradiated by gamma radiation, with doses between 0 and 16Gy.  Cell suspensions were irradiated in PBS by a 60Co source in doses between 0 and 16Gy, and incubated by 48h.  Then cell membranes were lysed in the presence of SYTOX Green and EMA dyes, preserving nuclear membranes.  Using this method, EMA-stained nuclei could be discriminated as those derived from dead cells, and SYTOX nuclei and micronuclei could be quantified.  Micronuclei percentages were found to be proportional to dose, (R2 = 0.997).  Only the highest dose (16Gy) could induce statistically significant increase of MN (p